Nutrition security, constraints, and agro-diversification strategies of neglected and underutilized crops to fight global hidden hunger - Ali, Akib; Bhattacharjee, Bijoya (Frontiers in nutrition (Lausanne), 2023)
Neglected and underutilized crop species (NUCS) or forbidden crops offer tremendous potential to combat malnutrition, poverty, and global hidden hunger. Since overdependence on a few dominant cereal crops, rice, maize, and wheat, is insufficient to meet the global food energy intake, the identification, genetic improvement, and implementation of various policies for wenumerates comprehensive comparative analyses of the nutrient profile of staple crops vs. potent underutilized crops with reference to cultivation constraints and climate resilience with different agro-diversification strategies. The research databases Scopus, JSTOR, Web of Science, EBSCO, Google Scholar, ScienceDirect, PubMed, and Academic Search were searched using relevant research queries. Out of 2,345 hits, 99 articles pertinent to the subject domain showed that underutilized crops are nutritionally superior, contain health-promoting bioactive components, and are more climate resilient than cereal crops. However, several constraints hinder the efficient utilization of these crops. Despite underutilized crops' many health benefits, improved cultivation techniques for the large-scale production of these crops are still in their infancy. Most of the time, however, the scientific knowledge gleaned from various study domains stays within the scientific community. The most crucial need of the hour, therefore, is an efficient network structure connecting governments, farmers, researchers, and people in business. Moreover, care must be taken to ensure that the policies of governments and INGOs/NGOs are properly implemented within a NUCS framework.